The truth according to Ember - Nava, Danica (Berkley Romance, 2024)
"A Native American woman who can't catch a break serves up a little white lie that snowballs into much more in this witty and entertaining rom-com by debut author Danica Nava. Ember Lee Cardinal has not always been a liar, not for anything that counted. But when her résumé is rejected thirty-seven times, she takes matters into her own hands. She gets creative listing her work experience and answers the ethnicity question on all job applications with a lie. No one wanted Native American Ember, but Caucasian Ember landed her dream accounting job on Park Avenue (Oklahoma). Accountant Ember thrives in corporate life--and her love life seems to be looking up, too: She starts to secretly date the IT guy and fellow Native, Danuwoa. But when they're caught in a compromising position on a work trip, a scheming mid-level executive threatens to expose them unless Ember manipulates the company's accounting books for him. Unwilling to allow Danuwoa to get fired and lose the financial support he needs for his sister, Ember agrees. As the blackmail continues to grow, so do Ember's lies. She must make the hard decision to either stay silent or finally tell the truth, which could cost her everything"--